2006
DOI: 10.1111/j.1550-7408.2006.00104.x
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Dihydropteroate Synthase Mutations in Pneumocystis jirovecii from Brazilian AIDS Patients

Abstract: Several studies from developed countries have documented the association between trimethoprim-sulfamethoxazole prophylaxis failure and mutations in the Pneumocystis jirovecii gene coding for dihydropteroate synthase (DHPS). DNA was extracted from Giemsa-stained smears of 70 patients with P. jirovecii pneumonia seen in Porto Alegre, Brazil, from 1997 to 2004. Successful PCR amplification of the DHPS locus was obtained in 57 of 70 cases (81.4%), including five cases (8.7%) that had used sulfa prophylaxis. No DHP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
7
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 11 publications
4
7
2
Order By: Relevance
“…A similar prevalence was reported in Australia (13%) [18] and Japan (29%) [19]. The limited data from developing countries seem to indicate that the prevalence may be lower there than in the developed countries: 0% in Brazil [20] and China [21], 7% in Zimbabwe [22], and 12% in Thailand [23]. By contrast, the rates reported in the United States were generally higher, ranging from 26% [3] to 81% [24].…”
Section: Discussionsupporting
confidence: 79%
“…A similar prevalence was reported in Australia (13%) [18] and Japan (29%) [19]. The limited data from developing countries seem to indicate that the prevalence may be lower there than in the developed countries: 0% in Brazil [20] and China [21], 7% in Zimbabwe [22], and 12% in Thailand [23]. By contrast, the rates reported in the United States were generally higher, ranging from 26% [3] to 81% [24].…”
Section: Discussionsupporting
confidence: 79%
“…The small sample sizes and relatively low frequencies among these studies preclude any conclusions about trends in prevalence over time. The overall prevalence of P. jirovecii DHPS mutations in China is similar to those reported from other developing countries (3,(8)(9)(10)(11)(12) but lower than those reported from developed countries (1-4) and may reflect the less frequent utilization of TMP-SMX or dapsone for PCP prophylaxis in developing countries.…”
supporting
confidence: 53%
“…We found that 56% of patients with PCP were infected with mutant P. jirovecii strains. This proportion stands in contrast to the lower frequencies reported from the African continent and other countries outside the industrialized world (8,12,23,25,30,34,40,46,48). The risk that P. jirovecii will develop mutations in the DHPS gene is higher for patients with PCP receiving sulfa drug prophylaxis than for those not receiving it (5,15,16,22,26,32,38).…”
Section: Discussioncontrasting
confidence: 49%